Election management in Cameroon : can elections Cameroon (Elecam) turn the tide of flawed elections? - Sall, .Babally (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.